Short-term cognitive impacts of electronic gaming machines with and without a skill-based component: A comparative laboratory study - Gainsbury, Sally M.; Philander, Kahlil S. (Frontiers in Psychiatry, 2022)
This study aimed to compare how consumers understand the role of skill and chance, experience cognitive distortions, and experience immersion based on use of either electronic gaming machines (EGMs) or skill gambling machines (SGMs; EGMs with a skill-based component). Participants (N=246, Mage=34 years, 56.91% female) in a laboratory experiment were randomly assigned to play a real EGM or SGM without funds and self-reported measures including intention to gamble, understanding of the role of skill and chance, erroneous gambling beliefs, previous gambling and gaming, and problem gambling severity. Participants demonstrated different deficits in understanding of the role of skill versus chance in determining outcomes following play. SGM players were more likely to increase their belief that a skill impacts outcomes and focused more on the game play experience. EGM players focused more on wins and personal performance. Intention to play both machines was predicted in both groups by greater experience of immersion during play and breadth of previous gambling, but breadth of previous gaming experience only predicted intent to play SGMs. The results revealed that both EGM and SGM players fail to understand how outcomes are determined, which is likely more problematic for EGM players as this reflects clear cognitive distortions. Further real-world testing is required to understand the extent to which SGMs harms may be different than EGMs, however these initial findings suggest that their risks appear comparable to EGMs while attracting individuals with more gaming experience.